Modification of Additional Check Valves and Tube Pressure to Enhance Hydram Pump Capacity and Performance for Agricultural Applications - Umar Husein Abdullah; Yusran Akbar; Lukman Martunis; Irhami Irhami; Sri Agustina; Muhammad Afdhal; Andriy Anta Kacaribu; Khairun Nisa (Jurnal Penelitian Pendidikan IPA, 2024)
Pump that operates automatically by relying on natural power from water without using great cost and trouble by pumping hydram. Hydram pumps are one of the types of pumps that are driven by kinetic power, it was discovered by a 1796 Montgolfier in Italy. The purpose is to determine the most optimal water speed of the hydram pump by using different numbers of pressure tubes and several check valves. This research uses a factorial Randomised Group Design (RGD) method. The first treatment is valve variation and the second is variation in the number of tubes. The results showed that the average river water flow velocity was 0.154 meters/second with an average water discharge of 2.61 m3/second under normal flow conditions. The average water flow in the intake pipe is 0.717 meters / second and the volume of water in the pipe is 15.19 liters with an average water discharge entering the intake pipe is 10.804 m3 / second. A combination of three valves and three tube treatments consistently produces greater water discharge than other combinations. The highest efficiency of the hydram pump is found in the combination of three checks.